New insight on the role of banana plant (Musa acuminata Cavendish) template in low-temperature synthesis of hydroxyapatite - Ferli Septi Irwansyah; Alfi Ikhlasul Amal; Eko Prabowo Hadisantoso; Atiek Rostika Noviyanti; Diana Rakhmawaty Eddy; Risdiana Risdiana (Results in Chemistry)
Hydroxyapatite (HA) is a highly biocompatible biomaterial widely used in biomedicine. Green template-based synthesis offers an eco-friendly approach to control nanoparticle morphology and agglomeration. The phytochemicals of banana plant parts are promising green templates for HA synthesis. Hydrothermal method was employed for HA synthesis, followed by FTIR, SEM, XRD, and PSA characterization. FTIR revealed water absorption in HAK150 and HAP150, while HAB150 showed minimal or absent absorption. SEM displayed cauliflower-like particle surface morphology. XRD indicated HAB150’s highest % crystallinity at 79.14 %, with a size of 26.05 nm. PSA showed the smallest HA particle size in HAB150 (1.30 µm), and HAK150 exhibited the lowest polydispersity index (0.789).